The grounded theory method: deconstruction and reconstruction in a human patient simulation context - Parker, Brian; Myrick, Florence (My University, 2011)
Certain modes of qualitative inquiry, such as grounded theory, can serve to uncover the abstract processes and broad conceptual themes influencing the personal experiences of undergraduate nursing students encountering clinical scenarios utilizing human patient simulators (HPS). To date insufficient research has been conducted to uncover the basic social-psychological processes encountered by students as they engage in a HPS-based clinical scenario. The authors assert that HPS-based learning experiences are in reality social endeavors that lead to the creation of socially negotiated knowledge and meanings relevant to the adult learner. To understand how grounded theory is suited to deriving answers to these questions, an analysis of the theoretical and philosophical foundations of grounded theory is undertaken. This critical analysis concludes with a discussion of specific considerations to be reflected upon by researchers when applying the inductively derived method of grounded theory in uncovering the social processes that occur within HPS-based clinical scenarios.
Keywords: grounded theory; human patient simulation; symbolic interactionism; social constructionism